Plasmonic gold nanoagents for cancer imaging and therapy. Issue 5 (4th May 2021) - Fu, Qinrui; Zhang, Xuan; Song, Jibin; Yang, Huanghao
Abstract: Gold nanoparticles (AuNPs) are a popular material in the field of nanoscience because of their excellent biocompatibility and unique physical and chemical properties, and have been widely used in the biomedical field. AuNPs have a simple preparation method, controllable shape and size, high electron density and atomic number, superparamagnetic properties, and radiation sensitization effect, and their optical absorbance can be adjusted to the required biological window; thus, AuNPs are suitable for cancer imaging (photoacoustic imaging, computed tomography, and magnetic resonance imaging), photothermal therapy, and radiotherapy. AuNPs can also be used as carriers to load photosensitizers or chemotherapeutic agents, and therefore, can also be used in photodynamic therapy and chemotherapy. In summary, AuNPs and their assemblies can simultaneously realize cancer diagnosis and treatment, providing a new idea in the development of precision medical treatment. Abstract : The review has summarized the biomedical applications of plasmonic gold nanoagents in cancer diagnosis, including NIR‐I PA imaging, NIR‐II PA imaging, ratiometric PA imaging, CT imaging, MRI and multi‐modal imaging; and in cancer therapies including PTT, PDT, radiotherapy, chemotherapy, and combined therapy.